Numerical Experiments Performed on the Imperial College Plasma Focus Machine: Dependence on Deuterium Pressure - Arwinder, Singh*; Saw, S. H.; Lee, S. (Institut Fizik malaysia, 2016)
In this paper, we use Lee’s 5 phase model code to configure the Imperial College Plasma focus machine operating in the pressure (P0 ) range from 0.5 Torr to 6 Torr to obtain the relationship between axial speed va , radial shock speedvs , piston speed vp and pinch temperature with P0 as follows: v a 14P 0.42 , v s 60P 0.60 , v p 40P 0.57 and Tpinch(max) 20 P 1.26 . 0 0 0 0 Using model parameters fitted from measured current waveforms we also computed the neutron yield versus pressure curve and found that the computed results curve has features of agreement with the measured curve of the Imperial College machine.